Saving the sun dragon - West, Tracey, 1965-; Howells, Graham (2014)
The dark magic the dragons encountered in their first adventure has made Ana's sun dragon, Kepri, sick and Drake's earth dragon, Worm, teleports the himself, Kepri, and the four young dragon masters far away from the castle in search of a cure--but the threat of the dark magic still remains
1st -3rd grades
Keywords: Dragons -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction